[The Consumer does Benefit from Feasible Price Stability]: A Comment [2] - Waugh, Frederick V. (Quarterly Journal of Economics, 1972)
Journal Article A Comment Get access Frederick V. Waugh Frederick V. Waugh Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 86, Issue 3, August 1972, Page 499, https://doi.org/10.2307/1880807 Published: 01 August 1972